Conceptualising the right to enjoy benefits of scientific progress and exploring its potential to enhance access to effective diagnosis and treatment of drug-resistant tuberculosis in South Africa - Shawa, Remmy Malama (Department of Public Health and Family Medicine, 2020)
The lack of access to effective diagnosis and treatment of drug-resistant tuberculosis (DR-TB) remains a persistent global challenge. Human rights arguments for access to treatment mostly focus on the right to health. However, a key challenge in access to effective diagnosis and treatment is the glaring absence of scientific research in neglected diseases such as TB. This thesis sets out to elaborate the right to enjoy the benefits of scientific progress and explore its potential to increase scientific research in DR-TB and consequently enhance access to effective diagnosis and treatment in South Africa. This research project was conducted using three interrelated sub-studies; a legal analysis sub-study which examines the current conceptualisation of the REBSP in international law; a policy analysis sub-study which interrogates South Africa’s legal and policy efforts towards the realisation of the REBSP and access to diagnosis and treatment for DR-TB; and a qualitative sub-study which explores the South African context regarding research and development (R&D) in general, and in DR-TB in particular. The qualitative sub-study included 17 stakeholders who are active in TB R&D, advocacy and policy work, from human rights and research institutions, government agencies, civil society organisations, and donor agencies. This thesis finds that the REBSP essentially ensures two things, namely the production of science and access to the benefits of scientific progress. However, most countries including South Africa have systems, policies and resources aimed at advancing the production of science but lack similar systems, policies and resources to purposely ensure the enjoyment of the benefits from scientific progress. Internationally, there is no clear guidance on the interpretation of the REBSP, making it difficult for states to domesticate it in their national policies and framework laws. A General Comment by a UN human rights monitoring body is therefore urgently needed to secure global consensus on the interpretation of the REBSP. In the meanwhile, South Africa can still draw inspiration for the REBSP and together with the right to health, use it to advance access to DR-TB diagnosis and treatment alongside many other interventions. To enable better access to effective diagnosis and treatment of DR-TB, this thesis recommends that South Africa i) develops systems that would make scientific progress and results accessible, and affordable; ii) removes system and regulatory barriers that hinder the conduct of research or that delay registration of new drugs; iii) monitors and regulates the conduct of third parties and prevent them from exploiting communities; iv) encourages pharmaceutical companies to provide free access to successful treatment and tools in communities where trials are conducted; and v) mobilises financial and technical resources and allocates them to DR-TB researchfrom drug discovery through to implementation science.